Experimental evaluation of the effect of cement type and seawater salinity on concrete offshore structures. (7th March 2022) - El-Khoury, Marinelle; Roziere, Emmanuel; Grondin, Frederic; Cortas, Rachid; Chehade, Fadi Hage
Highlights: Portland cement mortars were exposed to recomposed seawater at 35 and 70 g/L. Sadran's index C3 A + 0.27C3 S was used to study the influence of Portland cement composition. Expansion not affected by salinity, no significant influence of sulphate on microstructure. Stable brucite layer and calcium carbonate formed at the surface of exposed specimens. Continuous leaching of calcium hydroxide and formation of Friedel's salt were observed. Abstract: Although seawater exposure is relatively common, there are relatively few studies that couple the microscopic characterization to the mechanical/ macroscopic behavior of cement-based materials, by using a reformulation of seawater with all its multiple salts in the laboratory. The experimental study includes the effect of salinity, cement type, and specimens geometry on the degradation phenomenon. The seawater solution was recomposed in the laboratory by dissolving salts in deionized water. A stable brucite layer and calcium carbonate were formed at the surface of the exposed specimen. Continuous leaching of calcium hydroxide and formation of Friedel's salt was also observed. The mechanical properties of the attacked specimens remain equal or slightly lower than the control specimens even if significant changes could be observed in the microstructure. Due to seawater exposure, the hollow cylinders recorded the highest mass and volume gain thus the largest amount of products formed. These evolutions were accelerated with the increase of salinity contrariwise to expansion that was not affected by salinity increase and remained minor. Ordinary Portland cement recorded higher volume and weight gain than seawater resisting cement.